2001
DOI: 10.1016/s0952-1976(01)00023-9
|View full text |Cite
|
Sign up to set email alerts
|

Performance-based control system design automation via evolutionary computing

Abstract: --This paper develops a parallel evolutionary algorithm based design unification of linear control systems in both the time and the frequency domains under performance satisfactions. A speedup of near-linear pipelinability is observed for the parallelism implemented on a network of transputers of Parsytec SuperCluster. The approach is capable of tackling practical constraints such as actuator saturation or transportation delays, and can be automated by efficient evolution from plant step response data, bypassi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Compared with the working mechanism of a standard GA or an elitism GA, the Lamarckian mechanism of evolution is based on the theory that specific characteristics of an organism are directly inheritable by its offspring and survives the given environment [32,33]. In evolutionary algorithms, it has been shown that Lamarckian inheritance is an effective way to improve machine learning and convergence characteristics [34].…”
Section: Lamarckian Particle Filtermentioning
confidence: 99%
“…Compared with the working mechanism of a standard GA or an elitism GA, the Lamarckian mechanism of evolution is based on the theory that specific characteristics of an organism are directly inheritable by its offspring and survives the given environment [32,33]. In evolutionary algorithms, it has been shown that Lamarckian inheritance is an effective way to improve machine learning and convergence characteristics [34].…”
Section: Lamarckian Particle Filtermentioning
confidence: 99%
“…A number of automatically 'evolved' top-performing candidates will finally merge as optimal designs. Its unique search and adaptive learning power has facilitated design automation, transforming a manual iterative tuning process based on existing CAD or CACSD packages into CAutoCSD (Chong and Li 2002;Tan and Li 2001). The advantages of such CAutoCAD over traditional CACSD approaches include meeting multiple design objectives, offering design quality improved beyond the present performance bounds, and dramatically reducing design cycle and time-to-market.…”
Section: Evolution Enabled Cautocsdmentioning
confidence: 99%
“…The recent progress in evolutionary and soft computing techniques has enabled the replacement of the human trial-and-error based iterative process with a computer-automated one (Li et al 1995;Ng 1995;Tan 1997;Tan and Li 2001). More importantly, EC reshapes the way we think in designing and modelling engineering systems, and unleashes the uncharted potential of design engineering.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research work shows the capabilities of rule extraction from a trained network positions [30] [31] neurocomputing as a good decision support tool. Recently Evolutionary Computation (EC) has been successful as a powerful global optimisation tool due to the success in several problem domains [2][42] [43] [44] [45]. EC works by simulating evolution on a computer by iterative generation and alteration processes operating on a set of candidate solutions that forms a population.…”
Section: Introductionmentioning
confidence: 99%